Компетентнісна модель випускника магістратури – фахівця у сфері управління інтелектуальною власністю - Лунячек, Вадим Едуардович; Рубан, Наталія Павлівна; Рубашка, Володимир Петрович; Тіманюк, Валерія Миколаївна; Фесенко, Наталія Св'ятославівна (Українська інженерно-педагогічна академія, 2017)
В роботі розглядаються питання професійної підготовки фахівців у сфері інтелектуальної власності в умовах магістратури. Зокрема, запропонована компетентнісна модель магістра в сфері інтелектуальної власності, детально розроблені відповідні загальні і спеціальні компетентності, висвітлені програмовані результати навчання згідно з навчальними дисциплінами, що передбачені навчальним планом магістратури. В роботі надано також приклад схематичного розгляду окремих компетентностей фахівця в сфері інтелектуальної власності, наведено приклад такого аналізу для компетентності «Спроможність управляти інноваційними проектами». За основу взяті підходи до структури компетентності, передбачені Національною рамкою кваліфікацій України. Окрема увага приділяється висвітленню проблеми працевлаштування випускників магістратури – професіоналів у сфері інтелектуальної власності за умови оволодіння наведеними в роботі компетентностями. Представлені матеріали розроблені кафедрою креативної педагогіки і інтелектуальної власності Української інженерно-педагогічної академії з урахування багаторічного досвіду підготовки фахівців у цій сфері.

The paper highlights the issues of the professional training of professionals in the field of intellectual property within the framework of MA courses. In particular, the competence-based model of Master’s student in the sphere of intellectual property is presented, general and special competences are elaborated, programmed results of the training are presented in accordance with the academic disciplines specified in the Master’s program curriculum. The paper also presents an example of the schematic review of individual professional skills of a specialist in the field of intellectual property and illustrates an instance of such analysis for the competence “Ability to manage innovative projects”. The approaches to the competence structure provided by the National Qualifications Framework (NQF) of Ukraine have served as a basis for the research. Special attention is paid to the issue of employment of Master’s graduates – specialists in the sphere of intellectual property, providing they have acquired competences listed in this paper. Submitted materials have been elaborated by the staff of the Department of Creative Pedagogy and Intellectual Property of Ukrainian Engineering Pedagogics Academy in light of long-term experience of training specialists in this domain.
Competence-based model of a Master’s graduate – an intellectual property professional
Keywords: інтелектуальна власність; управління інтелектуальною власністю; компетентність; intellectual property; management of intellectual property; competence; competence-based model; training Masters in Intellectual Property